The optimum light condition to improve survival and growth rates of sutchi catfish (Pangasianodon hypophthalmus) larvae - Khairul Muttaqin Ismail (Kulliyyah of Sciences, International Islamic University Malaysia, 2020)
Sutchi catfish Pangasianodon hypophthalmus (Sauvage, 1878) is one of the most important freshwater fish species cultured in Southeast Asia. Artificial seed production of sutchi catfish in the hatchery is very important to supply enough seeds to the farmers in the aquaculture industry. However, the survival rates of its larvae were low when reared in the hatchery. Providing optimum rearing condition for sutchi catfish larvae in the hatchery should increase the seeds production. Light conditions were reported to influence the survival and growth of fish. Hence, this study was conducted to determine the optimum light conditions in term of light wavelength and light intensity for the rearing of sutchi catfish larvae. Three experiments were conducted, which were larval rearing, larval behaviour, and larval feeding behaviour experiment. For all three experiments conducted, five light wavelengths (white, blue, green, yellow and red lights) and four light intensities (1.40×10-4, 1.40×10-3, 1.40×10-2, and 1.40×10-1 µmol/m²/s) was used. The results for larval rearing experiment showed that the survival rates, growth rates, and production index were higher in red light and have the tendency to become higher in low light intensity (1.40×10-4 and 1.40×10-3 µmoles/m²/s). Next, in larval behaviour experiment, the larvae showed lower aggressive behaviour in red light and low light intensity (1.40×10-4 and 1.40×10-3 µmoles/m²/s). Lastly, feeding behaviour experiment showed that the larvae ingest a higher number of Artemia sp. nauplii under white, yellow, and red light wavelengths. Although there was no significant effect of light intensity towards the feeding behaviour, the number of Artemia sp. nauplii ingested tend to be higher in lower light intensity. Longer light wavelength such as red light with low light intensity resembles the light condition in the natural habitat of sutchi catfish. In conclusion, the red light wavelength under low light intensity (1.40×10-4 and 1.40×10-3 µmoles/m²/s) is recommended for the rearing of the sutchi catfish larvae.